S2RP: A Self –Heal Stable Routing Protocol for Disaster Scenario - et. al., Arun kumar Yadav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As population is increasing day by day, mobile nodes are being incremented in smart cities. Due to limited battery power, many nodes in the network become inactive during data transfer which leads to route breakage. Energy is a basic requirement for mobile ad-hoc network. Energy utilization is the critical part. The aim of this paper is to design a protocol i.e. S2RP, which finds stable, secure and energy efficient route. The proposed protocol avoids frequent link breakage and allows fast data transfer with low energy Consumption..